2005
DOI: 10.1007/s10620-005-2766-7
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and Systemic Effects of Oral Insulin Supplementation in Rats After Weaning

Abstract: Oral insulin has intestinal trophic effects in suckling animals. In mice, lower glucose and lipid levels may be seen when oral insulin is given after the weaning period. The purpose of the present study is to examine local and systemic effects of oral insulin supplementation in rats in the postweaning period. Immediately after weaning, Sprague-Dawley rats received either drinking water (controls) or oral insulin in their drinking water (1 U/ml) for either 1 week or 6 weeks. Intestinal mucosal parameters (bowel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
3
19
1
Order By: Relevance
“…We have also shown that oral INS had a trophic gut effect that was evidenced by increased bowel circumference, mucosal weight, mucosal DNA, and villous height. The maximal changes were observed in the first week of INS treatment, and most significant changes were observed in the proximal intestine (27). The results of the present study add to the evidence that oral INS has a trophic effect on the remaining small bowel following massive small bowel resection.…”
Section: Discussionsupporting
confidence: 73%
“…We have also shown that oral INS had a trophic gut effect that was evidenced by increased bowel circumference, mucosal weight, mucosal DNA, and villous height. The maximal changes were observed in the first week of INS treatment, and most significant changes were observed in the proximal intestine (27). The results of the present study add to the evidence that oral INS has a trophic effect on the remaining small bowel following massive small bowel resection.…”
Section: Discussionsupporting
confidence: 73%
“…Several in vitro and in vivo experiments have demonstrated that insulin and insulin-like growth factors enhance proliferation and diminish apoptosis in epithelial cells. We have previously observed similar effects of oral insulin on intestinal epithelial cell turnover in young rats after weaning [15], in rats after bowel resection [16] or adult rats after intestinal damage [17,18]. In contrast to these experiments, the current data suggest that OI supplementation in normal non-stressed adult rats exerts a mild inhibitory effect on microscopic intestinal mucosal parameters.…”
Section: Discussionsupporting
confidence: 45%
“…Group A-control rats (CONTR) were injected with vehicle and fed with regular chow diet; Group B-control rats were fed regular chow diet and water containing insulin at a concentration of 1u/1 ml as we described previously [15][16][17][18]; Group C-diabetic rats (DIAB) were injected with one dose of streptozotocin (STZ); Group D-DIAB-INS rats were injected with STZ and were treated with oral insulin similar to group B.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, these researchers have demonstrated that insulin activates the brush border membrane hydrolases in rat immature intestine by binding the hormone to its intestinal receptor and indirect triggering of the transcription of hydrolases genes and possibly by changes in intracellular polyamine concentrations [16]. We have recently shown that oral insulin supplementation exerts intestinal trophic effects, as well as systemic effects in rats when administered up to 6 weeks beyond the suckling period [17]. Since insulin has trophic gut effects, we hypothesized that insulin may have a beneficial effect on gut growth and recovery in different gastrointestinal disorders.…”
Section: Discussionmentioning
confidence: 99%